2000
DOI: 10.1007/s002219900289
|View full text |Cite
|
Sign up to set email alerts
|

A second look at the barriers of the medial basal hypothalamus

Abstract: The cell bodies of hypothalamic secretory neurons are localized in areas protected by the blood-brain barrier (BBB), whereas their axon terminals are localized in the median eminence, which lacks a BBB. This implies a complex barrier system, allowing neurons of the central nervous system to secrete into the blood stream without making the BBB leaky. In the present study, three experimental protocols were applied to clarify certain relevant aspects of the barriers operating in the medial basal hypothalamus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
160
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(171 citation statements)
references
References 0 publications
7
160
1
3
Order By: Relevance
“…Several reasons may explain why this central effect was only presented in obese mice, one of which might be the higher permeability of the blood-brain barrier in obese models (including ARC lesion mice and ob/ob mice) when compared with normal models (Skultetyova et al 1998). Several experiments have suggested that blood-brain barriers of obese models, such as ARC lesion mice and ob/ob mice, are more permeable than normal animals, especially under stress conditions (Sharma & Dey 1988, Skultetyova et al 1998, Peruzzo et al 2000. A second explanation for this consequence might be the different effective dosages needed for different species or models, as food intake is regulated according to body size and drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons may explain why this central effect was only presented in obese mice, one of which might be the higher permeability of the blood-brain barrier in obese models (including ARC lesion mice and ob/ob mice) when compared with normal models (Skultetyova et al 1998). Several experiments have suggested that blood-brain barriers of obese models, such as ARC lesion mice and ob/ob mice, are more permeable than normal animals, especially under stress conditions (Sharma & Dey 1988, Skultetyova et al 1998, Peruzzo et al 2000. A second explanation for this consequence might be the different effective dosages needed for different species or models, as food intake is regulated according to body size and drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Exactly how the loss of tanycytes and ependymocytes might contribute to glucoprivic deficits is not entirely clear. However, ␣ and ␤1 tanycytes, located in the ventrolateral two-thirds of the 3v, form long processes that contact neurons in the VMN (␣) (39) and ARC (␤1) (43,44), while the proximal portion of tanycytes contact the 3v CSF (39,44). Thus, tanycytes may provide metabolic and/or physical support for adjacent astrocytes and neurons (39).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, weight gain and insulin resistance from habitual consump-tion of palatable foods decrease insulin and leptin blood-brain barrier (BBB) penetrability (Caro et al, 1996;Kaiyala et al, 2000;Banks, 2003;Banks and Farrell, 2003;Woods et al, 2003) and their CNS effects (Couce et al, 2001;Banks and Farrell, 2003;Lindqvist et al, 2005;Porte et al, 2005), albeit some homeostatic hypothalamic areas lack BBB (Peruzzo et al, 2000;Ganong, 2000). The resultant brain insulin and leptin 'resistance' renders normal satiety signals even more ineffective (Erlanson-Albertsson, 2005;Isganaitis and Lustig, 2005) leading to further impairments in physiologic mechanisms regulating food intake (eg, overeating) and shifting the set point for energy homeostasis towards the development of overweight and obesity (Levine et al, 2003;Erlanson-Albertsson, 2005;Isganaitis and Lustig, 2005).…”
Section: Repetitive Palatable Food Consumption May Dysregulate Homeosmentioning
confidence: 99%